Mechanism of Multi-Physical Fields Coupling in Macro-Area Processing via Laser–Electrochemical Hybrid Machining (LECM) - Guangxian Li; Zhikun Su; Tingan Zhao; Wei Wei; Songlin Ding (Metals)
Laser–electrochemical hybrid machining (LECM) is promising in the processing of thin-wall parts, which avoids problems such as the weak stiffness of structures and thermal defects. However, while most studies focus on precision machining via LECM, few investigate the potential of this technique in macro-area processing. In this paper, the synergistic effects on the coupling of thermal field and electrochemical field on bulk material removal mechanisms in the LECM of additively manufactured Ti6Al4V are comprehensively analyzed experimentally and theoretically. According to the experimental results, LECM improved the material removal rate (MRR) by up to 28.6% compared to ECM. The induction of the laser increases local heating, accelerating the temperature rise of the electrolyte, eventually promoting the electrochemical reaction. The hydrogen bubble flow promotes overall heat convection between the electrode and workpiece, which facilitates the removal of the facial precipitates and increases the efficiency of electrochemical dissolution. Higher voltages and laser powers promote the formation of hydrogen bubble flow; meanwhile, they also aggravate laser energy scattering, limiting the overall machining efficiency. Additionally, laser irradiation causes the ablation and rupture of hydrogen bubbles, which weakens the bubble flow effect and ultimately decreases the material removal efficiency. This study reveals the underlying mechanisms of the joint effects of the laser field and electrical field in LECM, and the findings can provide valuable insights for the optimization of LECM parameters in industrial applications.